2016
DOI: 10.2147/ceor.s108730
|View full text |Cite
|
Sign up to set email alerts
|

Persistence, switch rates, drug consumption and costs of biological treatment of rheumatoid arthritis: an observational study in Italy

Abstract: ObjectivesThe aim of this analysis was to provide an estimate of drug utilization indicators (persistence, switch rate and drug consumption) on biologics and the corresponding costs (drugs, admissions and specialist care) incurred by the Italian National Health Service in the management of adult patients with rheumatoid arthritis (RA).MethodsWe conducted an observational retrospective cohort analysis using the administrative databases of three local health units. We considered all patients aged ≥18 years with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 21 publications
3
15
0
1
Order By: Relevance
“…Similar observational results focusing on long-term effectiveness have been reported in the literature reporting persistence between 22% and 41% by 3 years, but these studies did not observe patients for the length of time ours did [35,36]. A multitude of other observational and registry derived data are available which either followed patients for fewer years [37] or had followed considerably fewer patients [38].…”
Section: Discussionsupporting
confidence: 74%
“…Similar observational results focusing on long-term effectiveness have been reported in the literature reporting persistence between 22% and 41% by 3 years, but these studies did not observe patients for the length of time ours did [35,36]. A multitude of other observational and registry derived data are available which either followed patients for fewer years [37] or had followed considerably fewer patients [38].…”
Section: Discussionsupporting
confidence: 74%
“…When comparing switching to another TNFi as opposed to switching out of class, all-cause costs were higher in patients switching to a non-TNFi biologic DMARD compared with an alternative biologic TNFi [ 84 ]. Overall, RA patients with high rates of persistence (> 80%) had higher total healthcare costs, driven by higher pharmacy costs; however, the total non-pharmacy costs, including in- and outpatient visits and laboratory services, were lower than costs reported for patients with persistence rates of < 80% (Table 5 ) [ 85 , 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…The review also identified papers showing that patients who cycle through multiple biologic therapies incur higher costs and become less responsive to treatment [ 84 , 86 ]. Therefore, in the context of chronic diseases, it is beneficial to both individual patients and health systems to optimize patient journeys to ensure patients can cope with their treatment and remain compliant and persistent so as to avoid frequent cycling of multiple treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Die Kostenfrage von Therapiemodalitäten tritt zunehmend in den Vordergrund der Diskussionen und fließen in die Empfehlungen ein [3,6,[10][11][12][13][14][15]. Diese Notwendigkeit erschließt sich über die Zulassung v. a. hochpreisiger spezifischer Medikamentenentwicklungen der letzten zwei Jahrzehnte.…”
Section: Empfehlungen Und Leitlinienunclassified